1998
DOI: 10.1021/ma980241f
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbranched Poly(ε-caprolactone)s

Abstract: Novel hyperbranched poly(ε-caprolactone)s have been synthesized. The versatile synthesis utilizes AB2 macromonomers and allows the thermo-physical properties of the polymers to be tailored. The ε-caprolactone-based AB2 macromonomers were synthesized through living ring opening polymerization, using aluminum benzyloxide as the initiator. The aluminum benzyloxide initiated polymers were then functionalized with benzylidene-protected 2,2‘-bis(hydroxymethyl) propionic acid and subsequently deprotected to form the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
97
1
4

Year Published

1998
1998
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(103 citation statements)
references
References 39 publications
1
97
1
4
Order By: Relevance
“…Polyester dendrimers were prepared up to the fourth generation using even sterically congested cores like pentaerythritol in good yields using DMAP and DCC to promote ester formation. Since then, a number of research groups have utilized the benzylidene-protected bis-HMPA as a convenient building block [127,129,130,146,[150][151][152][153]. Synthesis of a dendritic macro-initiator for atom transfer radical polymerization [146].…”
Section: Scheme 12mentioning
confidence: 99%
“…Polyester dendrimers were prepared up to the fourth generation using even sterically congested cores like pentaerythritol in good yields using DMAP and DCC to promote ester formation. Since then, a number of research groups have utilized the benzylidene-protected bis-HMPA as a convenient building block [127,129,130,146,[150][151][152][153]. Synthesis of a dendritic macro-initiator for atom transfer radical polymerization [146].…”
Section: Scheme 12mentioning
confidence: 99%
“…Compared with dendrimers obtained from step-by-step synthesis, hyperbranched polymers could be considered as irregular analogues of the dendrimers with narrow polydispersity and predictable molecular weights [16], Moreover, hyperbranched polymers can easily be synthesized by direct one-pot polymerization based on functional ABx-type (x ≥ 2) monomers [17,18], which were better suited for application in highly functionalized globular production. Recently, hyperbranched PCLs (HPCLs) have been increasingly studied, because a homologous series of HPCLs with a range of molecular architectural variations (i.e., different lengths of linear backbone segments and different numbers of branching points) could be obtained by a series of novel synthetic approaches [19][20][21]. For instance, a series of HPCLs were synthesized through the moisture-sensitive catalyst-free polycondensation of AB2 macromonomers, and Jeongsoo Choi et al [22] investigated the thermal characteristics of HPCLs in conjunction with their branching features.…”
Section: Introductionmentioning
confidence: 99%
“…In 2004, Jeongsoo Choi and his colleagues [23] conducted a detailed study on the crystallization behaviors of three HPCLs with different molecular architectures. However, few methods are available to synthesize HPCLs [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…[27][28] This author also reported the synthesis of a second CL based AB 2 macromonomer via ring-opening polymerisation (ROP) of CL, using benzyl ester protected MPA and tin octanoate (Sn(Oct) 2 ). 28 Frechet et al reported the preparation of 4-(2-hydroxyethyl)-caprolactone which was then used to produce hyperbranched polyester in a one-pot strategy.…”
Section: Introductionmentioning
confidence: 99%